Nickel & Chromium Ions Release from Fixed Orthodontic Appliances in Iraqi patients (Mustansiria Dental Journal, 2018)
Nickel and chromium can cause hypersensitivity in some people , this study wasconducted to investigate the alteration in the nickel and chromium concentrations insaliva of patients with fixed orthodontic appliance.The investigation is comprised of 45 orthodontic patients .The selected sampledivided into 3 groups. The first group consisted of 15 patients with fixed appliancesin their upper & lower arches. The second group consisted of 15 patients with a fixedappliance placed only in the upper arch. The control group consisted of 15 patientswho were not undergoing orthodontic treatment.Nickel and chromium release was quantified with the use of an atomic absorptionspectrophotometr. The analysis of variance was used to determine if differencesexisted between the nickel and chromium release according to time interval. Foursamples of stimulated saliva were collected from each patient before insertion of fixedappliance, 1 week , 1month , and 2month after insertion of the appliance.A considerable variation in the concentrations of both nickel and chromium wasobserved. Significant differences were found between the no-appliance samples andthe samples obtained after insertion of the appliance.Nickel and chromium concentrations of saliva are significantly affected by fixedorthodontic appliances during the first 2 month of treatment.